Early childhood education - Bruce, Tina. (London : Hodder arnold, 2005)
Reflects developments in thinking and practice within the dynamic early years sector. This textbook discusses a range of subjects from theoretical and practical perspectives, including: the history of the early childhood, tradition and its pioneering thinkers, key principles in the modern context, the Birth to Three Matters framework, and more.
Includes bibliography reference and index.
Keywords: Early childhood education